Surface reaction of undoped AlGaN/GaN HEMT based two terminal device in H+ and OH- ion-contained aqueous solution - Mastura Shafinaz Zainal Abidin,; Shahjahan,; Abdul Manaf Hashim, (Universiti Kebangsaan Malaysia, 2013)
Gallium nitride is considered as the most promising material for liquid-phase sensor applications due to its chemical stability and high internal piezoelectric polarization. In this work, the sensing responses of undoped-AlGaN/GaN two terminal devices upon exposure to various pH levels in aqueous solution (a mixture of HCl and NaOH) as well as their possible sensing mechanism have been investigated. No reference voltage or gate voltage is applied. The changes in drain-source current, IDS as a function of pH level were evaluated. In the acidic region, there was an almost linear change in IDS where IDS decreased with the increase in pH level. Hence, the translated channel resistance increases with the pH level. High H+ ion concentration at low pH level which corresponds to the large net positive potential on the surface leads to the enhancement of the flow of electrons in 2DEG channel. As the pH level was increased towards neutral point in the acidic region which corresponds to the increase of OH- ion concentration, the net surface potential on the surface starts to be dominated by negative potential. As a result, the 2DEG channel starts to deplete which resulted in the increase of channel resistance. The estimated current and resistance change for sensing area of 1 mm2 and drain-source voltage, VDS of 1- 6 V are in the range of 2.16-80.1 mA/pH and 154.6-500.5 kΩ/pH, respectively. However, the linear decreases of IDS were not continuously observed in the basic region where OH- ions were dominant. The IDS levels were high, showing that the flows of carriers in 2DEG channel were enhanced again. The resistance was low and almost constant in the basic region. It seems to be resulted by the formation of thin Ga(x)O(y) layer on the AlGaN surface contributed by the interaction of OH- with the Ga-face surface. Hence, the net potential on the AlGaN surface seems to be dominated again by the net positive surface potential.